Manajemen operasional sarana dan prasarana stasiun kereta api berdasarkan tingkat kepuasan pengguna layanan - Lutfi, Muh Alkautsar; Maryam, Maryam; Tahir, Mukhtar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Improving the service process is the key which means not only increasing customer satisfaction, but also reducing costs, increasing added value and generating higher profits. The objectives of the study are to 1) Identify minimum service standards at Maros railway stations based on the Regulation of the Minister of Transportation Number 63 of 2019. 2) Analyze the level of conformity between the expectations and performance of the service provided by the service provider for passengers who use the services at the Maros train station.3) Analyze the level of passenger satisfaction with the quality of the infrastructure at the Maros train station. Research Methods Qualitative descriptive analysis using Importan Performance Analysis (IPA) through SPSS Ver.21. The results obtained 1) Based on the results of the identification of the SPM minimum service standards, it was found that several facilities and infrastructure were lacking in the Maros train station area, light fire extinguishers (APAR) were not up to standard, there were no evacuation routes for service users, there was no phone number for reporting security disturbances, there was no security post for security officers, parking lots were not up to standard, There is no counter for people with disabilities and there are no facilities and rooms for passengers with special needs 2) The Performance of Operational Management of Railway Station Facilities and Infrastructure has a level of compatibility between the level of performance and the level of interest/expectation of 98.86% which shows that the performance of the Operational Management of Railway Station Facilities and Infrastructure is satisfactory/good. 3) From the survey results, 6 (six) attributes were obtained that are included in Quadrant A. The six attributes are cleanliness at the station, cleanliness in the waiting room, number of seats in the waiting room, speed in responding to emergency conditions both on the train and at the station. Quadrant A shows that these attributes have a very high level of importance, but in their implementation they have not satisfied service users, so there is still a need to improve service performance.